Theory of Liquids and Other Disordered Media:A Short Introduction - Schirmacher, Walter (Springer, 2015)
This set of lectures provides an introduction to the structure, thermodynamics and dynamics of liquids, binary solutions and polymers at a level that will enable graduate students and non-specialist researchers to understand more specialized literature and to possibly start their own work in this field.